Diabetes mellitus and periodontitis: Inflammatory response in orthodontic tooth movement - Santamaria-Jr, Milton; Bagne, Leonardo; Zaniboni, Ewerton; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Felonato, Maíra; dos Santos, Gláucia Maria Tech; Mendonça, Fernanda Aparecida Sampaio; Esquisatto, Marcelo Augusto Marretto (Wiley, 2020)
Objectives: This study evaluated, in experimental model, the inflammatory alterations in gingival tissue and alveolar bone during the orthodontic tooth movement (OTM) in diabetes mellitus (D) and periodontitis (P). Setting and Sample Population: Forty male Wistar rats, 90 days old and weighing 300 g. Materials and Methods: The sample was divided into four groups (n = 10). OTM: orthodontic movement (10 days, 0.4 N force); P + OTM: periodontitis (ligature-induced periodontitis, 3-0 silk suture thread) and orthodontic movement; D + OTM: diabetes (Alloxan-induced diabetes, 150 mg/kg) and orthodontic movement; and D + P + OTM: diabetes, periodontitis and orthodontic movement. Tooth displacement was measured; fibroblast, inflammatory cells, osteoclast and blood vessels were quantified by histomorphometric analysis. Inflammatory markers, interleukin-6 (IL-6) and tumour necrosis factor (TNF-α) were quantified by ELISA (Enzyme-Linked Immunosorbent Assay) in gingival tissue. The fibroblastic growth factor (bFGF), transforming growth factor (TGF-β1) and the vascular endothelial growth factor (VEGF) were measured via Western blotting in the alveolar bone. The results were analysed by ANOVA and Tukey's test at a 5% significance level. Results: The quantification of inflammatory cells and the expression of IL-6, TNF-α, TGF-β1 and bFGF were increased in diabetes and periodontitis. However, the number of fibroblasts and blood vessels and the percentage of birefringent collagen fibres were higher in healthy animals. There was greater tooth displacement in the OTM group. Conclusion: Diabetes Mellitus modifies the inflammatory response. The increased expression of inflammatory markers IL-6, TNF-α and TGF-β1 in diabetic animals impairs neovasculogenesis and tissue reorganization during orthodontic tooth movement, which may be aggravated by periodontitis.
Keywords: diabetes mellitus; inflammation; orthodontic tooth movement; periodontitis